2003
DOI: 10.1080/jmf.14.1.35.38
|View full text |Cite
|
Sign up to set email alerts
|

Severity of obstetric complications and risk of adult schizophrenia in male patients: a case–control study

Abstract: The results seem to confirm the hypothesis that obstetric complications may contribute to increased vulnerability to the disease, in addition to genetic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Moreover, maternal influenza during the second trimester may impair fetal growth and predispose to obstetric complications and lower birth weight, both of which have been repeatedly found to increase the risk of subsequent schizophrenia [22,27]. Kendell et al [22], in a study of the seasonal fluctuations in birth weight in schizophrenia, found that schizophrenics born in the second quarter of the year (April to June, with a peak in May) had significantly lower birth weight than controls.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, maternal influenza during the second trimester may impair fetal growth and predispose to obstetric complications and lower birth weight, both of which have been repeatedly found to increase the risk of subsequent schizophrenia [22,27]. Kendell et al [22], in a study of the seasonal fluctuations in birth weight in schizophrenia, found that schizophrenics born in the second quarter of the year (April to June, with a peak in May) had significantly lower birth weight than controls.…”
Section: Discussionmentioning
confidence: 96%
“…Random biological events associated with schizophrenia include pregnancy and delivery complications (23,24), infections (25), and malnutrition (26). Lewis and Levitt (27) suggest that it is caused by an early (pre-natal or perinatal) static brain lesion with a long latency or a late (adolescence) brain disturbance of limited duration.…”
Section: Timing Of Diversion and Errorsmentioning
confidence: 99%
“…OCs constitute an early environmental factor that is a well-known source of neurological and behavioural abnormalities in non-psychotic populations (18,19). OCs have been considered possible risk factors of schizophrenia (20,21): there is considerable evidence that exposure to OCs is associated with an increased risk of developing schizophrenia in later life (22)(23)(24). Nevertheless, it remains unclear whether OCs represent an independent risk factor for schizophrenia, interact with genetic risk to increase liability, are themselves a manifestation of genetic liability for schizophrenia or are epiphenomena of developmental compromise in individuals who are already on a trajectory towards psychotic illness in adult life.…”
Section: Introductionmentioning
confidence: 99%